2018
DOI: 10.3389/fimmu.2018.02939
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Immune Mechanisms in Tolerance to Food Allergy

Abstract: Oral tolerance can develop after frequent exposure to food allergens. Upon ingestion, food is digested into small protein fragments in the gastrointestinal tract. Small food particles are later absorbed into the human body. Interestingly, some of these ingested food proteins can cause allergic immune responses, which can lead to food allergy. So far it has not been completely elucidated how these proteins become immunogenic and cause food allergies. In contrast, oral tolerance helps to prevent the pathologic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 128 publications
0
81
0
2
Order By: Relevance
“…Treg activation is one of the basic mechanisms of immune tolerance induction. Disturbed functioning of these cells results in a Th1/Th2 imbalance and produces an abnormal immunological response to external allergens [80].…”
Section: Intestinal Microbiota Immunity and The Development Of Immumentioning
confidence: 99%
“…Treg activation is one of the basic mechanisms of immune tolerance induction. Disturbed functioning of these cells results in a Th1/Th2 imbalance and produces an abnormal immunological response to external allergens [80].…”
Section: Intestinal Microbiota Immunity and The Development Of Immumentioning
confidence: 99%
“…Moreover, in the food industry, the aggregation processes of whey proteins from milk [ 6 ], wheat gliadin and glutenin [ 7 ], and peanut proteins [ 8 ] are some examples that are continuously studied. The formed aggregates affect not only the organoleptic properties of the final product, but also its digestibility, bioavailability of amino acids and, in some cases, they can even induce or reduce inadequate immune responses to a toxic protein [ 9 , 10 ].…”
Section: Setting the Frame And Initial Considerationsmentioning
confidence: 99%
“…Specific IgE antibodies induce degranulation of mast cells and release of mediators including cytokines, histamine, and proteases which in turn result in allergic symptoms. T regulatory cells (Treg cells) can produce inhibitory cytokines such as IL‐10 and TGF‐β and play a role in developing tolerance . Therefore, identifying the pattern of cytokine expression can give valuable insight into the mechanisms of food allergy.…”
Section: Introductionmentioning
confidence: 99%
“…T regulatory cells (Treg cells) can produce inhibitory cytokines such as IL-10 and TGF-β and play a role in developing tolerance. 14 Several studies link immunosuppression and especially tacrolimus to the development of transplant-aquired food allergy (TAFA) in liver transplanted children. [2][3][4]15 Lacaille et al 2 suggested that tacrolimus induced an imbalance between the Th1 and Th2 leukocyte subsets.…”
Section: Introductionmentioning
confidence: 99%